Higher Normal School and Annexed Institutes. Pedagogical, research, and cultural heritage contributions in Colombia (1936-1951) - Figueroa, Claudia (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2016)
This research presents the educational, research, and cultural heritage contributions of the Normal School, for the creation, development and promotion of institutes that extended its influence in the period 1936 to 1951. This work is based on the historical document review along with the social history of this educational institutions, with primary and secondary sources such as files found in Tunja and Bogota, including: the General Archive of the Nation and the Historical Archive of the UPTC. In this context, the question guiding this research was as follows: What were the educational, research and cultural heritage contributions of the Higher Normal School, for the creation, development and promotion of educational institutes that extended their influence in Colombia? The conclusion is that the Higher Normal School acquired models from humanism and science, ie science associated with teaching and knowledge for life, in order to build its own eclectic pedagogical model, which influenced the formation of teachers able to face the field of pedagogy, research, and high culture in their daily work. These aspects are evident in the bachelor´s degree and annexed institutes, which extended their educational influence and existence for the construction of the Colombian nation in the mid-twentieth century.